ANALISIS PRAKTIK PENGUNGKAPAN INFORMASI INTELLECTUAL CAPITAL DALAM LAPORAN TAHUNAN PADA PERUSAHAAN DELISTING DI BURSA EFEK INDONESIA - Susanti -; Melia Widayanti (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2018)
This study aims to analyze the disclosure of intellectual capital information in the annualreport.The population of this research is 11 companies delisting at BEI in 2013 until 2016 period. Thedetermination of sample used purposive sampling method. The data analysis method used in thisresearch is content analysis. The results of the analysis showed that the disclosure of intellectual capitalinformation on delisting companies from BEI is still quite low. Structural capital became the lowest andhuman capital became the highest revealed by 11 companies.